Lumbar spine X-rays for back pain: Still justified as a screening examination in South Africa - A. T. Scher (South African Journal of Radiology, 2003)
Standard teaching in the imaging approach to patients with back pain is that plain X-ray should only be obtained after 3 months of conservative treatment and thorough clinical examination and appropriate laboratory investigations. This approach, while appropriate in first-world countries, may lead to conditions such as tuberculosis of the spine being overlooked. An analysis was therefore made of 1 383 patients with complaints of lower back pain who were referred for X-ray of the lumbar spine. In 28 patients active spinal tuberculosis was diagnosed; in 8 of these patients the diagnosis had not been suspected clinically. It is concluded that in South Africa with its unsophisticated patient population and poor facilities, limited X-ray (lateral and AP view) of the lumbar spine is justified in patients presenting with back pain for the first time.